Increased circulating T helper 17 (TH17) cells and endometrial tissue IL-17-producing cells in patients with endometriosis compared with non-endometriotic subjects - Delbandi, Ali-Akbar; Mahmoudi, Mahmoud; Shervin, Adel; Farhangnia, Pooya; Mohammadi, Tahereh; Zarnani, Amir-Hassan (Reproductive biology, 2025)
Endometriosis, an inflammatory disease, is characterized by the aberrant presence of endometrial tissues at ectopic locations. Accumulating evidence suggests that inflammatory cells, such as interleukin-17 (IL-17)-producing cells, may be involved in the pathogenesis of endometriosis. This investigation assessed the frequency of IL-17A (commonly known as IL-17)-producing cells in peripheral blood mononuclear cells (PBMCs), ectopic, and eutopic endometrial tissues in patients with endometriosis compared to non-endometriotic subjects. PBMCs, ectopic, and eutopic endometrial tissues were collected from 23 patients with endometriosis. PBMCs and endometrial tissues from 20 non-endometriotic women were used as the control group. The frequency of T helper 17 (TH17) lymphocytes in PBMCs was assessed using flow cytometry, and the expression level of IL-17 in eutopic and ectopic endometrial tissues was evaluated through immunohistochemistry. The percentage of TH17 and IL-17-producing lymphocytes was significantly higher in the PBMCs of patients with endometriosis compared to non-endometriotic subjects (P < 0.01 and P < 0.001, respectively). The expression of IL-17 protein in ectopic (P < 0.001) and eutopic (P < 0.05) endometrial tissues of patients with endometriosis increased compared to controls' endometrial tissue. Furthermore, the eutopic endometrium of patients with endometriosis showed a higher expression of IL-17 protein than the eutopic endometrial tissue of control subjects (P < 0.05). The findings suggest that the higher frequency of IL-17-producing cells in the PBMCs and endometrial tissues of patients with endometriosis contributes to the pathogenesis of endometriosis. •Women with endometriosis exhibit a significantly higher frequency of IL-17-producing cells in their PBMCs compared to control.•The expression of IL-17 protein is markedly higher in endometrial tissues of patients with endometriosis compared to control.•Elevated IL-17 levels in endometrial tissues and PBMCs may play a crucial role in the pathogenesis of endometriosis.